Simplify the following expression:

4(20+12÷(5-3)

I need help with just this question plz.

4 answers

First, make sure your parentheses are balanced. You should have written
4(20+12÷(5-3))
Now, apply PEMDAS, doing the deepest parens first.
4(20+12÷2)
Inside each parens apply EMDAS
4(20+6)
4(26)
104
1.) 4(20 + 12) ÷ (5 - 3)
2.) (20 + 12) = 32
3.) (5 - 3) = 2
4.) 32 ÷ 2 = 16
5.) 4 + 16 = 20
all of you are wayy offfffff, the answer is 64
4(20+12÷(5-3)
5-3=2
20+12=32
32÷2=16
16x4=64
Ssshsy
Similar Questions
    1. answers icon 1 answer
  1. 1. Simplify the expression 7^9/7^3a.7^3*** b.7^6 c.7^12 d.1^6 2. Simplify the expression z^8/z^12 a.z^20 b.z^4 c.1/z^-4 d.1/z^4
    1. answers icon 15 answers
  2. 1. simplify the radical expression.√45 5√3 3√5 3√15** 15 2. Simplify the radical expression √180x^2 90x** 6x√5
    1. answers icon 1 answer
  3. Question 4 (1 point)Simplify the expression: 4x + 7 + 2x - 5 a 11x -3x b 6x + 12 c 6x +2 d 8x
    1. answers icon 2 answers
more similar questions